Pembinaan Pariwisata Berbasis Kearifan Lokal Melalui Pengelolaan Olahraga dan Pariwisata Sepeda Gunung (Mountain Bike) di Panorama Kayu Kolek Kabupaten Lima Puluh Kota Sumatera Barat - Irfan Arifianto; Roma Irawan; Romi Mardela (Jurnal Berkarya Pengabdian Masyarakat, 2021)
Mountain bike is one interesting sport that is attractive and rapidly growing in Indonesia as it is also strongly connected with tourism advancement. Particularly in Sumatera Barat Province, where it is well known with its beauty of nature and surely becoming tourist destination. One of them is located in Nagari Sikabu-kabu, Tanjung Haro, Padang Panjang which popular with the magnificent view of Kayu Kolek and has became the center of attention since last 2019 as this place has been selected for the first time for hosting one of prestigious events of mountain bike called Indonesia Induro Mountain Bike/INDURO, which normally taking place in Java Island. Regarding to that, it certainly brings out its own attractiveness and challenges at the same time especially for the community. INDURO is a reputable mountain bike racing competition in Indonesia. It has five series championship each year. Therefore, the lecturers of Sports Sciences Faculty with their expertise, within the Community Services Activities aim to support the partners in this area in order to be well-prepared in every aspects related to this sport activity. Prominently, with the escalation of the role of community based on the local wisdom and also the improvement of bike’s trail in becoming the national and international standard. Hence, eventually Kayu Kolek is expectedly to be hosting not only one event (INDURO) but multi events of mountain bike racing competitions such as XCO, XCC, downhill and more